Light regime and temperature on seed germination in Salvia hispanica L. - Emanoela Pereira de Paiva; Salvador Barros Torres; Francisco Vanies da Silva Sá; Narjara Walessa Nogueira; Rômulo Magno Oliveira de Freitas; Moadir de Sousa Leite (Acta Scientiarum. Agronomy, 2016)
This study evaluated the effects of different light regimes and temperatures on the germination of S. hispanica seeds and used a factorial scheme in a completely randomized experimental design, in which three light conditions were combined with six temperatures (constant 20, 25, 30 and 35°C and alternating 20-30 and 25-30°C), totaling 18 treatments with four 50-seed replications. The seeds were sown on blotting paper in transparent plastic boxes and then allowed to germinate in Biochemical Oxygen Demand germinators. The seeds were evaluated over a period of eight days with respect to the following variables: germination percentage, average germination time, shoot and root lengths, shoot and root dry weights and root-shoot ratio. The data were submitted to Tukey’s test (p ≤ 0.05%). The S. hispanica seed (beige colored) germination test can be carried out at constant (25°C) or alternating (25-30°C) temperatures. The germination of the seeds was indifferent to the light conditions evaluated; however, there was increased seedling growth and dry matter accumulation in the presence of light. The duration of the S. hispanica seed germination test can be five days, with the first count on the second day after sowing.